TAKHRIJ AL HADIS - Muh Farid Wadjedy; Muhammad Ali (MAHAD ALY JOURNAL OF ISLAMIC STUDIES, 2025)
This paper discusses the method of takhrij al-hadith as one of the essential disciplines in hadith studies. It aims to trace the origins of a hadith from primary sources, assess the validity of its chain of transmission (sanad) and content (matan), and determine its degree of authenticity. The study begins with an etymological and terminological definition of takhrij, followed by an explanation of its objectives, benefits, and practical steps involved in the process. The author also outlines the fundamental principles that must be mastered, such as proficiency in hadith wording, familiarity with canonical hadith collections, knowledge of musthalah al-hadith (hadith terminology), and the ability to evaluate the quality of transmitters through ‘ilm al-rijal (biographical evaluation). In addition, this paper highlights contemporary challenges in the practice of takhrij, including limited sources, insufficient Arabic language skills, and the widespread circulation of unauthenticated hadiths in the digital era. To address these challenges, the paper proposes solutions such as the use of digital tools, the consolidation of electronic libraries, and the integration of interdisciplinary approaches in hadith research. A case study of takhrij applied to a hadith from Sahih al-Bukhari is also presented to demonstrate the systematic application of the method. This paper asserts that mastery of the takhrij al-hadith method is vital for preserving the purity of Islamic teachings, enhancing academic credibility, and fostering scholarly ethics and critical thinking in the evaluation of religious information